Yoga Practice and the Preservation of Mental Health: The Global and National Perspectives - Tešović, Igor R. (Sociološki pregled, 2019)
It has been decades since yoga is no longer considered to be only an esoteric eastern discipline, but also a global phenomenon known for its encouragement of a healthy lifestyle. This paper is focused on analyzing the influence of yoga practice on people’s mental health in the global and national context of Republic of Serbia. The research is based on the analysis of the results of scientific research on the influence of yoga practice on the prevention and treatment of mental illnesses, as well as on the available sources on sociocultural characteristics of yoga practice. The results of the conducted research show that yoga practice has beneficial effects on mental health, meaning that its therapeutic potentials are used more frequently in different social spheres (health, education, sport etc.) both in the global and the national contexts.
Keywords: yoga; mental health; healthy lifestyle; mental disorders; therapeutic effects